FLOTATION SEPARATION OF NA-FELDSPAR FROM K-FELDSPAR BY MONOVALENT SALTS - Demir C.; Abramov A.A.; Çelik M.S. (My University, 2001)
A major proportion of feldspar ores contain both Na-feldspar (Albite) and K-feldspar (microcline or orthoclase) in the same matrix, usually in quantities of about 3–5% Na2O and K2O. Despite their identical crystal structures and physicochemical properties, flotation appears to be the only plausible method of separating these minerals. In this study, amine flotation, together with zeta potential, solubility, surface tension, and adsorption measurements has been studied as a function of monovalent salts in order to achieve a window of separation. The results reveal that at a particular salt concentration of NaCl and KCl flotation is maximised. A mechanism based on the adsorption of common ions, and ion exchange between the added salt of uncommon ions and those ions in the crystal matrix and the resultant surface modification is proposed to be responsible for the observed selective separation.